Cocoa Cultivation Technology and Cocoa Post-harvest Technology in The Kusuma Sari Women Farmers Group - Singapurwa, Ni Made Ayu Suardani; Suariani, Luh; Sudewa, Ketut Agung; Armaeni, Ni Komang (Research Collaboration Community (Rescollacom), 2024)
The primary product made in Candikusuma Village, Melaya District, Jembrana Regency, Bali, is cocoa. In order to boost community empowerment based on cocoa plantations, including cocoa cultivation and cocoa post-harvest technology, the PM-UPUD initiative seeks to support the growth of farmer groups and micro, small, and medium-sized enterprises. The operational techniques that are employed include direct practice, monitoring, assessment, surveys, and consultations. The Kusuma Sari Women's Farming Group, a farmer group affiliated with PM-UPUD (Community Service for Regional Superior Product Businesses), is situated in Candikusuma Village, Melaya District, Jembrana Regency, Bali. Partners encounter issues with the caliber of the cocoa beans they produce as well as insufficient knowledge about planting and caring for cocoa trees following harvest. The Kusuma Sari Women's Farmers Group now has the ability to grow cocoa and manage it post-harvest in an integrated and thorough way thanks to PM-UPUD initiatives. The application of cocoa bean fermentation technology and cocoa planting technology are among the talents that the PM-UPUD program partner group will use in 2024. Farming communities now have the ability to create fermented cocoa beans, which are more valuable to consumers. PM-UPUD initiatives have the potential to boost community welfare and revenue, particularly for those in the cocoa producer group.